WORKSHOP CLASSROOM ACTION RESEARCH UNTUK MENINGKATKAN SEMANGAT MENELITI GURU BIOLOGI SE-PROVINSI JAMBI DIMASA PANDEMI COVID-19 - Mia Aina; Ervan Johan W; Desfaur Natalia (Jurnal Pengabdian Masyarakat Pinang Masak, 2021)
Indonesia has an HDI (Human Development Index) ranked 107 out of 185. This shows that the quality of education in Indonesia has increased but is still quite low. Therefore, it is necessary to improve the quality of education in Indonesia. Efforts to improve the quality of education is to increase the professionalism of teachers. One of the ways to improve the quality of learning by teachers is through Classroom Action Research (CAR). Based on data from the google form questionnaire distributed, it is known that 50% do not understand about classroom action research. There are even some teachers who have never done CAR. So it is necessary to conduct classroom action research workshops to provide an understanding of CAR to MGMP biology and science teachers throughout Jambi Province. This workshop is carried out online by the Zoom cloud meeting application. Participants consisted of 49 biology teachers, chemistry teachers and science teachers throughout Jambi Province. The results of this service get a positive response from the teacher and increase the teacher's understanding of classroom action research